Bejewel your mind : effect of puzzle games on cognition - Bai, Xuechen (2010)
Results from past research have shown action video game experience enhances visual attention and visuospatial resolution. In this paper, the author examines the effect of puzzle game Bejeweled® 2 Action on visual abilities. In Experiment I, the Flanker Test and the Overcrowding Test were used to determine the differences in selectivity of visual attention and crowding effect in players and non-players of the game. A second experiment was conducted with 10 hours of training of Bejeweled® 2 Action for non-players and visual abilities were examined prior to and after the training. This study has successfully established that playing Bejeweled® 2 Action can lead to improved visual selective attention and a reduced crowding effect.